2012
DOI: 10.1681/asn.2012020210
|View full text |Cite
|
Sign up to set email alerts
|

The Eternal (Nocturnal) Quest for Better Dialysis Outcomes

Abstract: AS, Faul C, Sever S, Reiser J: CD2AP in mouse and human podocytes controls a proteolytic program that regulates cytoskeletal structure and cellular survival. J Clin Invest 121: 3965-3980, 2011 13. Jarad G, Miner JH: Albuminuria, wherefore art thou? J Am Soc Twenty years ago, Bernard Charra and colleagues from Tassin, France, published a seminal paper on the survival rate of patients undergoing thrice weekly 8-hour in-center hemodialysis (HD) treatments. 1 This publication, which still represents the gold stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thus, these three retrospective cohort studies and the accompanying editorials concluded that there is a strong association between longer HD TT (at a minimum frequency of three times per week) and improved survival. 20,21…”
Section: Non-randomized Retrospective Cohort Trialsmentioning
confidence: 99%
“…Thus, these three retrospective cohort studies and the accompanying editorials concluded that there is a strong association between longer HD TT (at a minimum frequency of three times per week) and improved survival. 20,21…”
Section: Non-randomized Retrospective Cohort Trialsmentioning
confidence: 99%